Female Rape in India: A Crime Against Nature - Osman, Idris Mohamed (Journal of Social Science and Humanities, 2025)
Female foeticide is a result of a gender bias social construction. It’s discrimination against women and believes them to be less valuable than men. Sons are preferred over daughters for many different reasons in this patriarchal society. Whether it be economically or socially, women are seen as weak and are less prized than men. Female foeticide is the process of finding out the sex of the foetus and undergoing abortion if it is a girl. Although female foeticide is illegal but still many people continue to practice it. Besides this, there are some communities which practice female infanticide which means the practice of killing the girl child once she is born.